A Horizontal Equity Analysis of the Minimum Tax Provisions: An Empirical Study - Anderson, Kenneth E. (The Accounting Review, 1985)
[Congress introduced the first version of the minimum tax provisions in the Tax Reform Act of 1969. Congress subsequently modified the minimum tax provisions with the Tax Reform Act of 1976 (TRA76), the Revenue Act of 1978 (RA78), and the Tax Equity and Fiscal Responsibility Act of 1982 (TEFRA). This study evaluates the TRA76, RA78, and TEFRA minimum tax provisions from the perspective of horizontal equity. The study is based on taxpayer data from the 1978 Individual Tax Model prepared by the Internal Revenue Service (IRS). Relevant individuals are classified into groups of equally-situated taxpayers based on expanded income. For each such group, the coefficient of variation (CV) is computed, and the three minimum tax structures are compared for their relative equity effects. The study generally concludes that the TRA76 add-on minimum tax best enhances horizontal equity.]